Changes in socioeconomic inequalities in food consumption among Brazilian adults in a 10-years period - Louzada, Maria Laura da Costa; Costa, Janaína Calu; Costa, Caroline dos Santos; Wendt, Andrea; Azeredo, Catarina Machado (Frontiers in Nutrition, 2022)
Objective To evaluate changes in socioeconomic inequalities in food consumption in Brazil over a 10-year period. Methods Data on 24-h recalls of adults (aged 20 years or more) from the 2008/9 (n = 26,327) and 2017/8 (n = 37,689). Brazilian Dietary Survey were analyzed. We used the Nova classification system to group food items and estimate the percentage of total energy from ultra-processed foods and plant-based natural or minimally processed foods. For sex and area of residence, we calculated the percentage points (p.p.) difference between the estimates for women and men, and rural and urban populations. Negative values indicate higher consumption among men or urban residents, positive values indicate higher consumption among women or rural residents, and zero indicates equality. For education and wealth levels we calculated the slope index of inequality (SII). The SII varies from −100 to 100, with positive values indicating higher consumption among more educated or wealthiest groups, negative values indicating higher consumption among less educated or poorest groups, and zero equality. Results Over the period, we observed a reduction in the percentage of total energy from plant-based natural/minimally processed foods from 13.0 to 12.2% and an increase in that of ultra-processed foods from 17.0 to 18.3%. The urban population and those in the wealthier and more educated groups presented higher consumption of ultra-processed foods and lower consumption of plant-based natural/minimally processed foods in both survey years. Over the 10-year period, there was an overall reduction of the socioeconomic inequalities, mainly explained by the greater increase in ultra-processed food consumption by the rural population and those from the poorest and less educated groups (difference for area −7.2 p.p. in 2008/9 and −5.9 p.p. in 2017/8; SII for education 17.7 p.p. in 2008/9 and 13.8 p.p. in 2017/8; SII for wealth 17.0 p.p. in 2008/9 and 11.2 p.p. in 2017/8). Conclusion Socioeconomic inequalities in food consumption decreased in Brazil, but it may lead to the overall deterioration of the dietary quality of the more vulnerable groups.